Sugar utilization in fermentation of nipa frond sap by saccharomyces cerevisiae - Mohd Noor, Siti Fatimah; Abdul Halim, Norhazimah; Muhamad, Aida; Musa, Muhammad Faiz; Alias, Nor Shahlina; Zulkifli, Nurnajihah (Penerbit UTHM, 2020)
In recent years, concerns about the reduction of energy and materials, as well as limits to the ecosystem's assimilation capacity of residues have been raised in the social, political and business arena. All fossil fuels and minerals are limited and non-renewable on a human scale. These resources are thus limited physically and more stringently, economically [1]. Dependency on fossil fuel as energy source increase the oil price and often leads to economic depressions. In addition, the gas emission produced by the combustion of fossil fuels also contributes to air pollution and global warming. Most countries also experience more and more international pressure on global warming issues. Hence, renewable and clean alternative fuels have received increasing attention for present and future utilization [2].